2021
DOI: 10.3390/su132413592
|View full text |Cite
|
Sign up to set email alerts
|

State Incentives and Sustainable Motivation System in the Health Sector

Abstract: Now that the pandemic has entered the second phase, in which countries are adapting to the crisis, governments need to determine incentives that will contribute to the sustainability of the health system and human health. Regarding this, human resources are a significant factor, which affects the sustainability of any system, and it is important to establish a relevant motivation system that will withstand the challenges that society will face in the coming period. The aim of this paper is to analyse three dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…A previous study by Nurgahayu et al [7] showed that there was no relationship between the incentives and the motivation of health workers in providing services. This research was contrary to the research conducted by Culafic et al [8] regarding state incentives and sustainable motivation systems in the health sector during the COVID-19 pandemic which incentives (bonuses) had an impact on motivation. Compensation had a significant positive effect on employee work motivation, which could be a driving force in increasing productivity and achieving organizational goals [9].…”
Section: Introductioncontrasting
confidence: 99%
“…A previous study by Nurgahayu et al [7] showed that there was no relationship between the incentives and the motivation of health workers in providing services. This research was contrary to the research conducted by Culafic et al [8] regarding state incentives and sustainable motivation systems in the health sector during the COVID-19 pandemic which incentives (bonuses) had an impact on motivation. Compensation had a significant positive effect on employee work motivation, which could be a driving force in increasing productivity and achieving organizational goals [9].…”
Section: Introductioncontrasting
confidence: 99%
“…Training in IPC and COVID-19 management, although a necessary component of epidemic management, was seen to inspire health workers who were involved in the response across the countries. The provision of training has also been reported to be a great spur to health worker efforts during the COVID-19 pandemic in Serbia [ 26 ]. Furthermore, the COVID-19 pandemic highlighted the value and necessity of evolving alternative approaches to training including virtual/online training or tele-applications to build the capacity of health personnel and to supervise them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Sierra Leone, the incentives included provision of equipment, capacity building of health workers, social media support system, including trainings on how to deal with the stigma associated with being a health worker and a risk allowance [ 25 ]. In Serbia, Culafic (2020) highlighted the significance of health worker incentives during the COVID-19 response [ 26 ]. During COVID-19, several strategies were employed to motivate health workers.…”
Section: Introductionmentioning
confidence: 99%
“…The job in itself, responsibility and advancement are also included in motivational factors. There must be some positive feelings about to duty that are related to these motivational factors mainly responsibility, achievement and recognition (Dulafid et al, 2021). Intrinsic motivation is the best cornerstone concept that creates an intersection between economy and psychology.…”
Section: Intrinsic Motivational Theorymentioning
confidence: 99%